Education on the Dangers of Environmental Chemical Exposure and Urine Protein Examination as Risk Factors for Impaired Renal Function Among Students at SDN 6 Kendari - Firda Yanti; Ani Umar; Jeoun Jung; Kraichat Tantrakarnapa; Sri Aprilianti Idris; Susanti Susanti; Muhammad Azdar Setiawan; Muhammad Sultanul Aulya; Kemal Idris Balaka; Ramadhan Tosepu; Tuti Dharmawati; Angriani Fusvita; Agung Wibawa Mahatva Yodha (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2026)
This community service activity aimed to improve primary school students’ knowledge regarding environmental chemical exposure and kidney health while introducing a simple renal screening approach as an educational awareness tool. The program was conducted in 2023 at Sekolah Dasar Negeri 6 Kendari and involved 30 grade 5 and grade 6 students selected using accidental sampling. The activities consisted of interactive, age-appropriate education sessions and preliminary screening using urine protein dipstick testing, together with serum urea and creatinine measurements. Knowledge scores increased from a mean of 3.13 (SD 1.93) before the education sessions to 8.83 (SD 1.02) after the sessions (p < 0.001), indicating substantial short-term improvement in understanding. Most participants had negative urine protein findings, with a small proportion showing low-level positivity, whereas biochemical values were generally within expected ranges. The screening results are presented descriptively to support awareness and should not be interpreted as a clinical diagnosis or as evidence of impaired renal function. Overall, the activity demonstrates the feasibility of integrating school-based health education with simple screening to promote awareness and engagement, providing a practical model for community health promotion while avoiding overstatement of clinical implications.